Strategic learning leadership: Unravelling the relationship between talent management and organizational leadership competencies - Tonda Priyanto; Agus Heruanto Hadna; Indrayanti Indrayanti; Muhadjir Darwin (International Journal Labs, 2024)
In today's dynamic economic environment, developing leadership competencies is vital for organizational success. Despite the growing recognition of the importance of leadership development, there is a notable research gap in understanding how specific talent management strategies impact the enhancement of leadership competencies. This study investigates how talent management (TM) and strategic learning leadership (SLL) contribute to cultivating organizational leadership competencies (OLCs) in Indonesian state-owned companies. The study utilised a quantitative study with a random convenient sampling method using Google Forms in Indonesian state-owned companies. Data were collected from across 25 state-owned companies, with a total of 605 respondents participating. Statistical analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the hypotheses. The findings indicate that SLL significantly mediates the relationship between TM and OLCs, enhancing the impact from 17.2% to 58.5%, with SLL showing a stronger influence on OLCs compared to TM. Overall, these factors account for 55.2% of the impact on OLCs. This study contributes to the existing literature by highlighting the critical role of strategic learning leadership in enhancing leadership competencies, offering valuable insights for organizations aiming to develop effective leadership through strategic approaches.